Relationship Between EEG Electrode and Functional Cortex in the International 10 to 20 System. Issue 6 (November 2018) - Ives-Deliperi, Victoria L.; Butler, James Thomas
Abstract : Introduction: In this study, we attempted to define the variability in the anatomical relationship between scalp EEG electrodes and eloquent cortical function, as inferred from fMRI. Methods: MRI-compatible fiducial markers were positioned at locations of CZ, C3 and C4, T3 and T4, and F7 and F8 in 10 healthy subjects. Well-validated fMRI paradigms were administered to activate primary motor cortex and language regions, and the distance between these brain regions and fiducial markers was measured. Results: C3/C4, Cz, F8/F7, and T3/T4 were located 16 to 42 mm from the BOLD signal in the primary motor cortex for the contralateral hand and foot, and anterior and posterior language areas, 11 to 21 mm of which was the distance from the skin to the underlying cortex. Conclusions: There is considerable variation in the distance between the fMRI-defined primary motor and language cortex and the most contiguous electrode. This distance likely underestimates the true variability of electrode placement in relation to eloquent cortex in people with epilepsy or structural brain disorders. Because the evidence indicates that spikes on scalp EEG reflect discharges from the cortex that is of the order of 3 cm by 3 cm or greater in size, the demonstrated variability of electrode placement in relation to the cortex may be clinically and surgically important in individual patients.